EML4-ALK rearrangement in primary malignant fibrous histiocytoma of the lung treated with alectinib: A case report - Zhang, Shuai; Liao, Xuqiang; Chen, Jiawei (Frontiers in Oncology, 2022)
Primary malignant fibrous histiocytoma of the lung (PMFHL) is extremely rare. It is more common in the right lung and has no specific symptoms. Lymph node metastasis is rare, but hematogenous metastasis is more common. The common metastatic sites are the brain and bone. In this study, a 59-year-old male patient was diagnosed with PMFHL with brain metastasis due to persistent cough and blood in the sputum for the past week. Genetic testing revealed EML4-ALK gene rearrangement (fusion). We first used alectinib in a patient with advanced PMFHL with EML4-ALK gene rearrangement (fusion) accompanied by brain metastasis. The treatment was effective and successfully delayed the development of the disease. Satisfactory results were observed, with an overall survival time of 19 months. Therefore, genetic testing in PMFHL and the choice of treatment plan are important. Local treatment methods, including surgery and radiotherapy, are important when the disease is less advanced. Multidisciplinary discussion is recommended for the best prognosis.